2011
DOI: 10.5402/2011/731917
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Ultrasound Examination of the Leeds Enthesitis Index in Psoriatic Arthritis and Rheumatoid Arthritis

Abstract: Objective. To compare scores for the Leeds enthesitis index in psoriatic arthritis and rheumatoid arthritis using clinical assessment and ultrasonography (US). Design. Swelling and tenderness of the enthesis was assessed at six sites: lateral epicondyles of humerus (LE), medial condyles of femur (MC), and the insertion of the Achilles tendon (AT). US assessed “inflammatory activity” (power Doppler signal, oedema, tendon thickening, and bursal swelling) and “damage” (erosions and enthesophytes). Results. 94 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 13 publications
0
12
0
5
Order By: Relevance
“…Data were an alyzed using the SPSS v. 20 On the other hand the total damage score as well as the damage score at the 6-LEI points showed insignifi cant difference between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Data were an alyzed using the SPSS v. 20 On the other hand the total damage score as well as the damage score at the 6-LEI points showed insignifi cant difference between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are studies that could not confirm the specific link between enthesitis and SpA [ 35 , 36 ]. Paramarta et al found the same prevalence of entheseal involvement in SpA and RA patients [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Swollen or painful Achille's tendon is an important sign of enthesitis and is part of the items of the Leeds Enthesitis Index and the EARP questionnaire …”
Section: Discussionmentioning
confidence: 99%